Application Of The Problem Based Learning Model With Media Learning Videos To Increase Motivation Learning Class VI Gondangan Jogonala State Primary School - Susilowati Susilowati (Universitas Sebelas Maret, 2022)
The problem based learning model is one of the models used in science learning. The problem based learning model is a learning approach that uses real world problems as a context for students to learn critical thinking and problem solving skills, as well as to gain essential knowledge and concepts from the subject matter. The use of the Problem Based Learning Model and learning video media can increase learning motivation and learning outcomes for class VI students at SD Negeri Gondangan Jogonalan.Online learning with a problem based learning model and learning video media can improve the learning outcomes of class VI students at SD Negeri Gondangan. This can be seen from the value of learning outcomes in each lesson content which has increased from the pre-cycle activities, the first cycle to the second cycle, with an average value of 81.53 or 90%. On average, each student has achieved a KKM score of 70.